Madhusudan Dattatraya Sathe. Regional planning : an areal exercise. Poona, India : Saraswat Prakashan, 1973. 229 p. - Ruiz Chiapetto, Crescencio (Estudios Demográficos y Urbanos, 1976)
MADHUSUDAN DATTATRAYA SATHE, Regional Planning. An Areal Exercise, Poona, India, Saraswat Prakashan, 1973.